12 Invited lecture: High-throughput functional genomics – An emerging field in head and neck cancer research. Issue 5 (May 2015) - Brakenhoff, R.H.
<x xml:space="preserve">Abstract</x> Introduction Head and neck squamous cell carcinomas (HNSCC) belong to the six most frequent tumors worldwide, and the incidence is rising. HNSCCs develop in the mucosal linings of the upper aerodigestive tract, and are preceded by prenoplastic changes, a phenomenon coined as "field cancerization". Risk factors for HNSCC are smoking and excessive consumption of alcohol. Moreover, there are genetic predisposition syndromes, most particularly Fanconi anemia, associated with a very high risk for HNSCC. In recent years it became evident that also infection with the human papillomavirus (HPV) causes HNSCC, particularly tumors that arise in the oropharynx. HNSCC caused by HPV is a distinct class of tumors, both at the clinical and molecular level. Despite the application of combined treatment modalities that may severely impact quality of life with disfigurement, problems with speech and swallowing, the prognosis of HNSCC remains disappointing. New effective and less toxic treatments are urgently awaited. As a first step we tried to identify novel druggable gene targets. Material and methods Two tumor cell lines were transfected with a genome-wide siRNA library, and cell survival assayed. Sublibraries of lethal siRNAs were rescreened on a larger panel of HPV-positive and HPV-negative cell lines as well as primary fibroblasts. Data were normalized and compared by bioinformatics. Druggable gene targets were mined. Results We identified 362 genes that cause cell death in cancer cell lines, while only 20% of these cause cell death in primary fibroblasts. There were large differences between cell lines. One of the gene hits for which a small molecule inhibitor was available was analyzed in more detail. The inhibitor showed high efficacy in xenografted mouse models. Conclusion In head and neck cancer only few druggable oncogenic mutations occur. Nonetheless using functional genetic screens and genome editing methods multiple gene targets can be identified that might be exploited for improved treatment protocols.